(untitled) (Research, Society and Development, 2022)
The Amazon occupies an extensive and rich area in the Brazilian territory, where numerous types of research are carried out with the objective of promoting sustainable exploration, preserving its riches, and safeguarding its potential and its biodiversity. Thus, this work aims to enhance or facilitate the production of new bioproducts, through the results of the analysis of the seeds (S), pulp (P) and peel (C) of the fruits of the species Cucurbita maxima., thus obtaining values at the characterization of its components for bioactive compounds, where the results obtained, determined average values of proteins (12.54% S, 7.58% P and 15.75% C); average values ​​of total minerals through the ash, (2.63% S, 4.66% P and 4.77% C). For the ranges in the nutritional analysis in the flour of the seeds studied, the following values were obtained: moisture (33.55%), ash (2.63%), lipids (21.98%), carbohydrates (31.93%), proteins (12.51%) and energy value (375.50 Kcal.100g-1). The sum of unsaturated fatty acids (AGI), 82.40%, of saturated fatty acids, SFA (17.6%), and of monounsaturated fatty acids, MUFA (25%). The minerals found through the analysis of ash in the parts of the fruit (seeds: 2.635%; pulp: 4.664%; and rind: 4.775%) shows that the rinds are in greater quantity. The results obtained in this work will serve as a basis for the use or use of discarded parts of the fruit, with the possibility of generating good products for the Amazon region.